Data from: Early evolution of the angiosperm clade Asteraceae in the Cretaceous of Antarctica - Barreda, Viviana Dora; Palazzesi, Luis; Tellería, María Cristina; Olivero, Eduardo B.; Raine, J. Ian; Forest, Félix (2020)
This dataset contains the following tables: - Table S1. Pollen morphological data matrix of extant and fossil taxa - Table S2. Calibration scenarios - Table S3. GenBank accession numbers - Table S4. Fossil data Fil: Barreda, Viviana Dora. Consejo Nacional de Investigaciones Científicas y Técnicas. Museo Argentino de Ciencias Naturales. División Paleobotánica; Argentina. Fil: Olivero, Eduardo B. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Palazzesi, Luis. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales; Argentina. Fil: Palazzesi, Luis. Royal Botanic Gardens; Reino Unido Fil: Tellería, María Cristina. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo; Argentina Facultad de Ciencias Naturales y Museo